2016
DOI: 10.1017/s1368980016002871
|View full text |Cite
|
Sign up to set email alerts
|

The effects of restaurant nutrition menu labelling on college students’ healthy eating behaviours

Abstract: Findings support the role menu labelling can play in encouraging a healthier lifestyle for college students. College students who are Generation Y desire healthier menu options and accept nutritional labels on restaurant menus as a way to easily and expediently obtain nutrition information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
5
18
1
Order By: Relevance
“…Our findings align with the results of Roseman et al 16 in the southwest United States. They found that the addition of calories on the menus had a positive impact on the study participants.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our findings align with the results of Roseman et al 16 in the southwest United States. They found that the addition of calories on the menus had a positive impact on the study participants.…”
supporting
confidence: 93%
“…They found that the addition of calories on the menus had a positive impact on the study participants. 16 Moreover, the results of Vanderlee et al 25 in Canada align with our findings, especially that the majority of participants noticed that calorie values were displayed on menus. Furthermore, the study conducted by Radwan et al 26 in the United Arab Emirates uncovered similar results to ours in that most of the participants supported the policy of mandatory menu labeling.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Healthy food consciousness is on the rise among young adults at the global level [8]. The improved awareness of healthy food promotes the addition of nutritional labelling on food and food menus by food sellers [9]. Restaurants provide information on food calories and serve food-conscious customers by charging premium prices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Conklin, Lambert, and Cranage (2005) indicated that the inclusion of nutritional information resulted in the selection of healthier food choices. Roseman, Joung, Choi, and Kim (2017) also showed that menu information about calories had a significantly positive impact on students' intention to select lower-calorie foods. In addition to evaluating the influence of calorie information on food selections by consumers, recent studies have also evaluated the effect of exercise information on calorie intakes by consumers.…”
Section: Effect Of Menu Labeling With Different Types Of Information mentioning
confidence: 90%